Mastering English Grammar through the Implementation of Interactive Grammar Game Applications in English Classes - sih pratiwi, Dyah; Sugandi, Bastian; Fakhrunnisa, Fakhrunnisa (ELT-Lectura, 2025)
Abstract: Grammar is one of the most important elements of the English language. There is not a single word in English that does not involve grammar. In fact, a lot of English proficiency tests use grammar as one of the parts. Mastering grammar is as easy as mastering writing and speaking. This makes grammar has a big contribution in mastering English. The purpose of this research is to improve English Grammar skills through the implementation of a grammar game application in English classes in the digital era. This application contains grammar exercises and interactive training games and is very contemporary. The approach used in this study is a quantitative experimental method, employing a pretest-posttest control group design. The study involved two groups: an experimental group and a control group. The data analysis process is divided into two stages. The first stage involves analyzing the pretest and posttest data, while the second stage focuses on analyzing data from the questionnaire on the application's use. For the pretest and posttest data, a t-test is applied. Specifically, an independent t-test, which is a type of parametric test, is used to compare two independent groups. The analysis is based on two criteria: (1) if the significance value (2-tailed) is greater than 0.05, it indicates no significant difference between the groups; (2) if the significance value (2-tailed) is less than 0.05, it indicates a significant difference. The comparison of pretest and posttest scores between the experimental and control groups serves to address the research question about the effectiveness of the English Grammar Practice application in enhancing grammar skills. The results suggest that the application has a positive impact. Although the experimental group initially scored lower on the pretest than the control group, the posttest results showed that the experimental group outperformed the control group, demonstrating the effectiveness of the application in improving grammar proficiency.